DIFFERENT CORE INTERACTING BOSON-FERMION MODELAND SPECTROSCOPIC FACTOR ANALYSIS - Nabeil Ibrahim Fawaz (مجلة جامعة الانبار للعلوم الصرفة, 2012)
ABSTRACT:The level structure of 125Te by considering 124Te as a core for positive parity low-lying states has been investigated. Spectroscopic factor for both pick-up and stripping reactions were deduced according to the Interacting Boson-Fermion Model(IBFM) and compared with experimental results. Considering 126Te as a core gives best description to the 125Te nucleus.